S59 Chemo-immunotherapy of mesothelioma: depletion of established, suppressive CD4 T cells is critical to achieving cures in a murine model. (2nd December 2011) - Steer, H J; Cleaver, A; Nowak, A; Robinson, B; Lake, R
Abstract : Introduction: Mesothelioma is incurable and new treatment strategies are urgently needed. It has long been recognised that malignant cells can be attacked by the immune system but immunotherapy is only starting to emerge as an additional modality of treatment for cancer. The crucial role that helper CD4 T cells play in orchestrating CD8 T cell and other anti-tumour responses has only recently been appreciated. However the CD4 population contains effector and suppressive subsets with diverse and opposing functions. Although the effects of pemetrexed on tumour immunity are still being defined, gemcitabine is known to synergise with immunotherapy by causing tumour cell death, releasing tumour antigen and depleting suppressive immune cells. We investigated the role that different types of CD4 cell play in CD8 anti-tumour immune responses and how the CD4 response could be best manipulated to optimise outcomes to chemo-immunotherapy. Methods: Thy1.2+ve balb/c mice bearing mesothelioma tumours expressing the neoantigen haemagglutinin (HA), were treated with gemcitabine and adoptive transfer of tumour antigen (HA) specific thy1.1+ve CD8 T cells and thy1.1+ve CD4 cells which had been differentiated in vitro into Th1s, Th2s, Th17s or regulatory T cells (Tregs). The activity of the adoptively transferred cells in vivo was tracked by identifying recovered thy1.1+ve cells by flow cytometry. Results: In the prophylactic treatment setting, in vitro differentiated tumour antigen specific Th1s led to rejection of tumours inoculated 1 day later in around 40% of mice. However there was minimal activity against established, gemcitabine-treated tumours. Recovery of adoptively transferred CD8 T cells revealed that in established tumours, CD4s were unable to help cognate CD8 cells expand and infiltrate tumours. However if endogenous CD4s were depleted prior to treatment then CD8 tumour infiltration was significantly increased and cures were seen in around two-thirds of mice. Conclusions: These results suggest that once a tumour is established, an over-riding endogenous suppressive CD4 response prevents effector CD4s from helping CD8 T cells to eradicate tumours. Removal of suppressive CD4 cells was critical to achieving cures with chemo-immunotherapy.